2019
DOI: 10.2478/aiht-2019-70-3277
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study of salt content in bakery bread in Zagreb, Croatia

Abstract: Reducing salt content in bread is the essential part of a national strategy for salt reduction with the goal of long-term national general health improvement. In this study we have analysed salt content in three types of bread available in 25 small and five national industrial bakeries in Zagreb, Croatia. Samples of white wheat bread, dark wheat bread, and other types of bread were collected, and the salt content was determined with the Mohr method. Salt content varied widely between bakeries, with an average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Concerning the fact that the current male adolescents have consistently higher levels of physical activity and sport participation, as well as lower levels of sedentary time [57], a rational explanation might be that the higher dietary intake in the current male population [58] combined with generally poorer nutrition habits in Croatian young men [59] may have led to the greater overweight and obesity prevalence. In addition, the traditionally spicy food and increased salt intake in the Croatian population [59][60][61][62] and high prevalence of elevated BMI could have likely influenced the proportion of urban young males with elevated blood pressure [60,63].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the fact that the current male adolescents have consistently higher levels of physical activity and sport participation, as well as lower levels of sedentary time [57], a rational explanation might be that the higher dietary intake in the current male population [58] combined with generally poorer nutrition habits in Croatian young men [59] may have led to the greater overweight and obesity prevalence. In addition, the traditionally spicy food and increased salt intake in the Croatian population [59][60][61][62] and high prevalence of elevated BMI could have likely influenced the proportion of urban young males with elevated blood pressure [60,63].…”
Section: Discussionmentioning
confidence: 99%
“…The average salt content was higher than the Croatian National Regulation on Cereals and Cereal Products (1.4%). The recommendation of the study was that to teach bakers in reducing salt content and to continuously monitor and implement legal provisions (Aždajic, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, study of the Faculty of Food Technology has shown that a significant number of small bakeries still do not comply with the regulations. Bread from large shopping centers, which is usually imported as a frozen form from other countries, which is not subject to the regulation, also contained a high content of salt [66]. 4) The success of the project implementation was analyzed by determining the urine salt excretion in 2008 and 2015.…”
Section: Action Plan For Salt Reduction In Croatia Ministry Of Health...mentioning
confidence: 99%